Patrol report - Beaver, W. (1951)
The patrol report gives details of the Baiaia murders and descriptions of the pursuit and arrest of the murderers in the district lying between the Fly and Bamu Rivers. Also includes descriptions of the terrain and the Girara peoples and their customs.
Manuscript reference: NLA MS 3842.
Beaver was resident magistrate in the Daru district, Papua New Guinea during 1951 when the Baiaia murders occurred. He conducted the patrol in which the murderers were arrested.
Keywords: Murder -- Papua New Guinea; Papuans -- Social life and customs; Magistrates